2010
DOI: 10.1038/cr.2010.97
|View full text |Cite
|
Sign up to set email alerts
|

High-efficiency somatic reprogramming induced by intact MII oocytes

Abstract: Somatic nuclei can be reprogrammed into a pluripotent state by nuclear transfer, cell fusion and expression of transcription factors. However, these reprogramming processes are very inefficient, which has greatly hindered efforts to elucidate the underlying molecular mechanisms. Here, we report a new reprogramming strategy that combines the advantages of all three reprogramming methodologies into one process. We injected nuclei from cumulus cells into intact MII oocytes. Following activation, 80% of the recons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Mouse tetraploid embryos were successfully generated by fusing two blastomeres within the zona pellucida and can also be produced by injecting somatic cells into intact MII oocytes 7 . A previous study of tetraploid mouse embryo development showed that tetraploid embryos can undergo compaction and form cavities similar to diploid embryos 8 ; furthermore, tetraploid mouse embryos could be recovered on the 15th day of gestation, but their development was retarded 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Mouse tetraploid embryos were successfully generated by fusing two blastomeres within the zona pellucida and can also be produced by injecting somatic cells into intact MII oocytes 7 . A previous study of tetraploid mouse embryo development showed that tetraploid embryos can undergo compaction and form cavities similar to diploid embryos 8 ; furthermore, tetraploid mouse embryos could be recovered on the 15th day of gestation, but their development was retarded 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an intriguing study showed a dramatic improvement in the efficiency of ESC line derivation following SCNT 63 . Instead of using enucleated oocytes, the authors injected somatic cells into intact MII oocytes and confirmed the reprogramming capability of these cells.…”
Section: Somatic Cell Nuclear Transfermentioning
confidence: 98%
“…Recently, an intriguing study showed a dramatic improvement in the efficiency of ESC line derivation following SCNT. 63 Instead of using enucleated oocytes, the authors injected somatic cells into intact MII oocytes and confirmed the reprogramming capability of these cells. The reported efficiency of ESCs generation per injected oocyte was 30%, and the pluripotent ESCs were shown to have undergone epigenetic reprogramming at the Oct4 promoter.…”
Section: Escs From Primates By Means Of Scnt Encourages Further Consimentioning
confidence: 99%
“…In the presence of oocyte nuclei, the transferred cell nuclei underwent NEBD and entered pre-metaphase I stage 5 times faster than the enucleated group. This phenomenon was also observed in mice by using an intact oocyte as the recipient cytoplast [63]. To verify oocyte nucleus capability for cell reprogramming, a reverse nuclear transfer (RNT) procedure was performed.…”
Section: Second Metaphase Stage Cytoplasts As Recipientsmentioning
confidence: 99%